Resveratrol-Induced Xenophagy Promotes Intracellular Bacteria Clearance in Intestinal Epithelial Cells and Macrophages - Al Azzaz, Jana; Rieu, Aurélie; Aires, Virginie; Delmas, Dominique; Chluba, Johanna; Winckler, Pascale; Bringer, Marie-Agnès; Lamarche, Jérémy; Vervandier-Fasseur, Dominique; Dalle, Frédéric; Lapaquette, Pierre; Guzzo, Jean (Frontiers in Immunology, 2019)
Autophagy is a lysosomal degradation process that contributes to host immunity by eliminating invasive pathogens and the modulating inflammatory response. Several infectious and immune disorders are associated with autophagy defects, suggesting that stimulation of autophagy in these diseases should be beneficial. Here, we show that resveratrol is able to boost xenophagy, a selective form of autophagy that target invasive bacteria. We demonstrated that resveratrol promotes in vitro autophagy-dependent clearance of intracellular bacteria in intestinal epithelial cells and macrophages. These results were validated in vivo using infection in a GFP-LC3 zebrafish model. We also compared the ability of resveratrol derivatives, designed to improve the bioavailability of the parent molecule, to stimulate autophagy and to induce intracellular bacteria clearance. Together, our data demonstrate the ability of resveratrol to stimulate xenophagy, and thereby enhance the clearance of two invasive bacteria involved life-threatening diseases, Salmonella Typhimurium and Crohn’s disease-associated Adherent-Invasive Escherichia coli. These findings encourage the further development of pro-autophagic nutrients to strengthen intestinal homeostasis in basal and infectious states.